Experimental study on hydraulic fracturing behavior of frozen clayey silt and hydrate-bearing clayey silt. (15th August 2022) - Ma, Xiaolong; Jiang, Dandan; Sun, Youhong; Li, Shengli
Highlights: Fracability of clayey silt hydrates with low saturation was confirmed. Heterogeneity of clayey silt hydrates leads to non-uniform fracture propagation. 2 MPa minimum in-situ stress difference controlling fracture propagation direction. Abstract: There are critical problems in the field trials of natural gas hydrate (NGH) production, such as low production rate, limited recovery range and short period of stabilized production. Reservoir stimulation is a potential means to promote gas recovery from NGHs since previous studies have proved that gas production of other unconventional gas reservoir can be highly enhanced by hydraulic fracturing. However, few studies pay attention to the hydraulic fracturing behavior of clayey silt NGH reservoir. In this work, the effects of sediment properties and fracturing fluid parameters on fracture initiation, propagation and morphology were experimentally investigated by hydraulic fracturing of frozen clayey silt and methane hydrate-bearing clayey silt. The results indicated that the uneven distribution of ice in sediments led to non-uniform fracture propagation phenomenon, such as single-wing fracture and fracture deflection. The fracturing fluid with injection rate of 90 mL/min was conducive to the formation of complex fractures in sediments, which indicated that that increasing injection rate could greatly increase the effect of reservoir reconstruction. When the axial pressure (8 MPa) was 2 MPa higher than the confining pressure, the fracture propagated in the direction perpendicular to the minimum principal stress, which revealed the magnitude of minimum in-situ stress difference controlling the fracture propagation direction. In addition, this work showed the fracability of clayey silt hydrates even with low saturation, which revealed the feasibility of hydraulic fracturing of marine methane hydrate reservoir.